THE SOUTH-EASTERN ANATOLIA PROJECT FACTOR ON WATER MANAGEMENT AND ENERGY DEMAND IN TURKEY - Yuksel, Ibrahim (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2018)
Alternative energy sources especially hydro-power is very important in Turkey. Because hydro-power industry is closely linked to both water management and renewable energy production and thus has an important role, in cooperation with the international community, and in striving for sustainable development in a world where billions of people still lack access to safe drinking water and adequate energy supplies. The south-eastern Anatolia Project (GAP) which covers one-tenth of Turkey's total land area. GAP will have an installed capacity of 7,460 MW. In the project, more than 329 hydropower plants is projected to add a total installed capacity of 19,699 MW, thus the total number of hydro plants is to bring to 483 and will be the total installed capacity of 34,592 MW by 2020. The project includes the construction of 22 dams and 19 hydroelectric power plants on the Euphrates and the Tigris rivers. It is planned that upon completion, over 1.8 million hectare of land will be irrigated and 27 billion kWh/y hydroelectric will be generated. This paper deals with hydro energy management for energy demand and GAP factor in Turkey.
Keywords: Water management; energy demand; hydropower; GAP; Turkey; RENEWABLE ENERGY; HYDROELECTRIC POWER; FUTURE; ELECTRICITY; IRRIGATION; POLICIES; Environmental Sciences & Ecology